Control of Vortex Helicity With a Quarter-Wave Plate in an Er:YAG Ceramic Solid State Laser - Qiyao Liu; Yongguang Zhao; Wei Zhou; Jianing Zhang; Li Wang; Weichao Yao; Deyuan Shen (IEEE Photonics Journal, 2017)
In this paper, we research the characteristics of the Laguerre-Gaussian (LG01) beams generated in an Er:YAG ceramic solid state laser pumped by an annular beam. The generated two LG01 beams (LG0,+1 and LG0,−1 modes) were found to have different thermally induced polarization behaviors and alternately existed in the resonator; then, a novel method was proposed and experimentally demonstrated to control the vortex helicity using a simple quarter-wave plate.